Engineering multiple U7snRNA constructs to induce single and multiexon-skipping for Duchenne muscular dystrophy. - Goyenvalle, A; Wright, J; Babbs, A; Wilkins, V; Garcia, L; Davies, K (2012)
Duchenne muscular dystrophy (DMD) is a fatal muscle wasting disorder caused by mutations in the dystrophin gene. Antisense-mediated exon skipping is one of the most promising approaches for the treatment of DMD but still faces personalized medicine challenges as different mutations found in DMD patients require skipping of different exons. However, 70% of DMD patients harbor dystrophin gene deletions in a mutation-rich area or "hot-spot" in the central genomic region. In this study, we have developed 11 different U7 small-nuclear RNA, to shuttle antisense sequences designed to mask key elements involved in the splicing of exons 45 to 55. We demonstrate that these constructs induce efficient exon skipping both in vitro in DMD patients' myoblasts and in vivo in human DMD (hDMD) mice and that they can be combined into a single vector to achieve a multi skipping of at least 3 exons. These very encouraging results provide proof of principle that efficient multiexon-skipping can be achieved using adeno-associated viral (AAV) vectors encoding multiple U7 small-nuclear RNAs (U7snRNAs), offering therefore very promising tools for clinical treatment of DMD.